Enhancing cardiac reprogramming via synthetic RNA oligonucleotides - Jiabiao Hu; Conrad P. Hodgkinson; Richard E. Pratt; JaeWoo Lee; Bruce A. Sullenger; Victor J. Dzau (Elsevier, 2021)
Reprogramming scar fibroblasts into new heart muscle cells has the potential to restore function to the injured heart. However, the effectiveness of reprogramming is notably low. We have recently demonstrated that the effectiveness of reprogramming fibroblasts into heart muscle cells (cardiomyocytes) is increased by the addition of RNA-sensing receptor ligands. Clinical use of these ligands is problematic due to their ability to induce adverse inflammatory events. To overcome this issue, we sought to determine whether synthetic analogs of natural RNA-sensing receptor ligands, which avoid generating inflammatory insults and are nuclease resistant, would similarly enhance fibroblast reprogramming into cardiomyocytes. Indeed, one such stabilized RNA, ICR2, increased the expression of cardiomyocyte-specific mRNAs in reprogrammed fibroblasts. Moreover, ICR2 enhanced the ability of reprogramming factors to produce cardiomyocytes with mature sarcomeres. Knockdown assays indicated that the effects of ICR2 were mediated by the RNA-sensing receptors Rig-I and TLR3. In addition, ICR2 reduced the effective dose and number of reprogramming factors needed for efficient reprogramming. In summary, the synthetic RNA oligonucleotide ICR2 is a potential therapeutic agent to enhance cardiac reprogramming efficiency.